EVALUATION OF POTENTIAL DRUG INTERACTIONS IN PRESCRIPTIONS FOR PATIENTS IN INTENSIVE CARE UNITS - Garske, Cristiane Carla Dressler (2017)
The identification and the interaction of drugs are directly related to patient´s safety and are highly relevant within the hospital. Current analysis identifies and evaluates potential drugs interactions within prescribed pharmacotherapy. The study, undertaken between August and December 2015, comprises 308 prescriptions of 195 patients hospitalized in the UTI of a university hospital. Micromedex® database identified interactions. Further, 101 out of 308 prescriptions revealed at least one drug interaction, with a total of 173 interactions with 71 patients, of which 43 were males with an average age of 61,9 years. Mean hospitalization period in the ICUs was 7 days. The 101 prescriptions with drug interactions totaled 1,349 drugs, at an average of 13,3 drugs/patient/day. The identification of these interactions avoids therapeutic failure and toxicity.